A closer look at strengthened readings of scalars. Issue 1 (January 2018) - Simons, Mandy; Warren, Tessa
The majority of the extensive experimental and theoretical literature on scalar strengthening assumes that the phenomenon is uniform across all types of scalars. The experiment reported here contributes to the growing evidence against scalar uniformity, while also exploring the suggestion of Van Tiel, Van Miltenburg, Zevakhina, and Guerts, (2014) of the role of boundedness in the observed variation. The current experiment utilizes a novel approach to exploring the interpretation of scalars, and also investigates the content of strengthened interpretations.